Left sided chest pain: a case report of Boerhaave syndrome mimicking acute coronary syndrome - Hoo, Fan Kee; Lee, Sing Hong; Sumon, Md. Shariful Hasan; Wan Sulaiman, Wan Aliaa; Mohd Sazlly Lim, Sazlyna; Basri, Hamidon (International Online Medical Council, 2013)
The Boerhaave syndrome (Boerhaave 1742) or spontaneous rupture of the oesophagusis an unusual condition, which is rarely encountered in clinical practice. It is crucial to establish the diagnosis of this condition promptly. The mortality and morbidity is directly proportional to the delay in diagnosis and the severity of mediastinitis due to mediastinal contamination. Although its clinical features had been well described, an occasional case do present with some diagnostic difficulties unless there is a high index of suspicion.Here, we report a patient who presented with left sided chest pain that mimics acute coronary syndrome and diagnosed as Boerhaave syndrome.